Consensus of linear multi‐agent systems subject to communication delays and switching networks. (25th January 2017) - Lu, Maobin; Liu, Lu
Summary: In this paper, the consensus problem for linear multi‐agent systems subject to nonuniform time‐varying communication delays and jointly connected switching networks is investigated. Two cases, known communication delay and unknown communication delay, are considered, respectively. For each case, both distributed dynamic state feedback control law and distributed dynamic output feedback control law are proposed. By establishing some technical lemmas, it is shown that the proposed distributed control laws can solve the consensus problem, respectively. Copyright © 2017 John Wiley & Sons, Ltd.